Poverty, Inequality, And Social Disparities During China's Economic Reform - Dollar, David, 1954- 1954- (The World Bank, 2007)
China has been the most rapidly growing economy in the world over the past 25 years. This growth has fueled a remarkable increase in per capita income and a decline in the poverty rate from 64 percent at the beginning of reform to 10 percent in 2004. At the same time, however, different kinds of disparities have increased. Income inequality has risen, propelled by the rural-urban income gap and by the growing disparity between highly educated urban professionals and the urban working class. There have also been increases in inequality of health and education outcomes. Some rise in inequality was inevitable as China introduced a market system, but inequality may have been exacerbated rather than mitigated by a number of policy features. Restrictions on rural-urban migration have limited opportunities for the relatively poor rural population. The inability to sell or mortgage rural land has further reduced opportunities. China has a uniquely decentralized fiscal system that has relied on local government to fund basic health and education. The result has been that poor villages could not afford to provide good services, and poor households could not afford the high private costs of basic public services. Ironically, the large trade surplus that China has built up in recent years is a further problem, in that it stimulates an urban industrial sector that no longer creates many jobs while restricting the government's ability to increase spending to improve services and address disparities. The government's recent policy shift to encourage migration, fund education and health for poor areas and poor households, and rebalance the economy away from investment and exports toward domestic consumption and public services should help reduce social disparities